Controlling Epileptiform Activity with Organic Electronic Ion Pumps. (11th April 2015) - Williamson, Adam; Rivnay, Jonathan; Kergoat, Loïg; Jonsson, Amanda; Inal, Sahika; Uguz, Ilke; Ferro, Marc; Ivanov, Anton; Sjöström, Theresia Arbring; Simon, Daniel T.; Berggren, Magnus; Malliaras, George G.; et al.
<x xml:space="preserve">Abstract</x> In treating epilepsy, the ideal solution is to act at a seizure's onset, but only in the affected regions of the brain. Here, an organic electronic ion pump is demonstrated, which directly delivers on‐demand pure molecules to specific brain regions. State‐of‐the‐art organic devices and classical pharmacology are combined to control pathological activity in vitro, and the results are verified with electrophysiological recordings.